IPEM topical report: results of a 2020 UK survey on the use of online treatment monitoring solutions for IMRT/VMAT. (15th November 2021) - W Stevens, Simon; Moloney, Stephen; Bangiri, Anna; Blackmore, Andrew; Hart, Clare; Holmes-Smith, William; Pooler, Alistair; Rixham, Philip; Doolan, Paul
Abstract: Numerous commercial technologies for online treatment monitoring (OTM) in radiotherapy (RT) are currently available including electronic portal imaging device (EPID) in vivo dosimetry (IVD), transmission detectors and log files analysis. Despite this, in the UK there exists limited guidance on how to implement and commission a system for clinical use or information about the resources required to set up and maintain a service. A Radiotherapy Special Interest Group working party, established by Institute of Physics and Engineering in Medicine was formed with a view to reassess the current practice for OTM in the UK and an aim to develop consensus guidelines for the implementation of a system. A survey distributed to Heads of Medical Physics at 71 UK RT departments investigated: availability of OTM in the UK; estimates of workload; clinical implementation; methods of analysis; quality assurance; and opinions on future directions. The survey achieved a 76% response rate and demonstrated that OTM is widely supported in the UK, with 87% of respondents indicating all patients should undergo OTM. EPID IVD (EIVD) was the most popular form of OTM. An active EIVD service was reported by 37% of respondents, with 84% believing it was the optimal solution. This demonstrates a steady increase in adoption since 2012. Other forms of OTM were in use but they had only been adopted by a minority of centres. Financial barriers and the increase of staff workload continue to hinder wider implementation in other centres. Device automation and integration is a key factor for successful future adoption and requires support between treatment machine and OTM manufacturers. The survey has provided an updated analysis on the use of OTM methods across the UK. Future guidance is recommended on commissioning, adoption of local tolerances and root-cause analysis strategies to assist departments intending to implement OTM.